2011
DOI: 10.1017/s0022215111002313
|View full text |Cite
|
Sign up to set email alerts
|

Functional results of pharyngo-laryngectomy and total laryngectomy: a comparison

Abstract: The additional measures involved in pharyngo-laryngectomy do not confer any functional disadvantage, compared with total laryngectomy, but only if the procedure is non-circumferential. Functional results of circumferential pharyngo-laryngectomy are worse than those of both non-circumferential pharyngo-laryngectomy and total laryngectomy. If oncologically possible and safe, it is better to keep a pharyngo-laryngectomy non-circumferential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 10 publications
4
23
3
Order By: Relevance
“…Few studies have attempted to investigate the effects of prior XRT on functional outcomes in laryngeal and hypopharyngeal SCC patients undergoing surgical intervention. Gadepalli et al did not find a significant difference in postoperative functional outcomes when stratifying by salvage status. However, the authors acknowledged that their laryngopharyngectomy group had a relatively low proportion of salvage patients (20%).…”
Section: Discussionmentioning
confidence: 91%
“…Few studies have attempted to investigate the effects of prior XRT on functional outcomes in laryngeal and hypopharyngeal SCC patients undergoing surgical intervention. Gadepalli et al did not find a significant difference in postoperative functional outcomes when stratifying by salvage status. However, the authors acknowledged that their laryngopharyngectomy group had a relatively low proportion of salvage patients (20%).…”
Section: Discussionmentioning
confidence: 91%
“…As for the association between pharyngocutaneous fistula and oral feeding, a recent study of 191 patients with head and neck cancer who had undergone microvascular reconstruction showed that defects of the hypopharynx and radiotherapy before surgery strongly predicted postoperative difficulty in swallowing, as assessed by whether patients were eventually able to take food orally or remained dependent on nasogastric tubes . In addition, merely the presence of a pharyngocutaneous fistula is known to independently impair swallowing outcome . We found that in patients who undergo a pharyngolaryngectomy, pharyngocutaneous fistulas resulted in delayed starting of postoperative oral feeding: these patients took more than 3‐fold longer than patients without pharyngocutaneous fistulas to initiate free oral feeding.…”
Section: Discussionmentioning
confidence: 67%
“…Additional resection of pharyngeal mucosa significantly increases the incidence of pharyngocutaneous fistula formation after total laryngectomy. 17,18 However, relatively few studies have reported the incidence of postoperative pharyngocutaneous fistula after pharyngolaryngectomy: 5.0% (6 of 119), 19 22% (12 of 55), 11 30.6% (15 of 49), 20 and 52.5% (52 of 160). 4 In our study, we found a relatively low proportion (6%) of fistulas after pharyngolaryngectomy, surgical closure of pharyngocutaneous fistulas having been performed in 3.4% of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations